Legal Problems of Regulation of Electronic Land Certificates In the Legislation System in Indonesia - Suyanto, Suyanto (Budapest International Research and Critics University, 2021)
The digitalization of legal products continues to develop as an effort to provide convenience and transparency of public services, as well as certificates of land rights as proof of land registration rights in the form of paper (land books) or analogues based on Law no. 5 of 1960 concerning Agrarian Principles and Government Regulation no. 24 of 1997 concerning Land Registration, with the issuance of Law no. 11 of 2020 concerning Job Creation provides legal norms for electronic certificates of land rights which are regulated by Permen ATR/BPN No. 1 of 2021 concerning Electronic Certificates, so that with the new regulation, land registration products are in the form of electronic (e-certificates), to the significant difference in the form of the certificate, there are legal issues regarding the position of the Job Creation Law, Permen ATR/BPN No. 1 of 2021 with the UUPA and PP No. 24 of 1997 in the legal system in Indonesia. This research is normative juridical with a statutory and conceptual approach. ATR/BPN Ministerial Regulation No. 1 of 2021 concerning Electronic Certificates based on Law no. 12 of 2011 its position is under PP No. 24 of 1997 so that according to the principle of lex superiori derogate legi inferiori the provisions of the Ministerial Regulation as long as it regulates land registration may not conflict with a Government Regulation which has a higher legal degree. Land registration norms are regulated in the UUPA and PP No. 24 of 1997, while the Job Creation Act and ATR/BPN Regulation No. 1 of 2021 is not a legal norm that regulates land registration but as a new norm regarding the granting of land rights in the form of electronic certificates as evidence of the election of land rights.